Mediators in Psychological Treatments for Anxiety and Depression in Adolescents and Young People: A Protocol of a Systematic Review - Conejo-Cerón, Sonia; Taubner, Svenja; Heinonen, Erkki; Adler, Asta; Barkauskiene, Rasa; Di Giacomo, Dina; Ioannou, Yianna; Mestre, Jose M.; Henriques, Margarida Rangel; Mota, Catarina Pinheiro; Protić, Sonja; Raleva, Marija; et al. (Frontiers in Psychology, 2021)
Introduction: Anxiety and depressive disorders are a significant problem that starts in adolescence and should be addressed early to avoid chronic mental conditions. There is strong evidence to demonstrate that psychotherapy is effective in the treatment of these disorders, however, little is known on mediators and mechanisms of change of psychological treatment in adolescents and young adults. Understanding the pathways through which psychological treatments operate will facilitate more effective treatments. Aim: We aim to conduct a systematic review, exploring the available evidence on mediators of psychological treatments for anxiety and depression in adolescents and young adults. Methods: A systematic search has been performed on PubMed and PsycINFO databases to identify studies from inception to 23rd February 2020. Eligible studies include prospective, longitudinal, and case-control designs that have enrolled adolescents and young adults presenting with depression and/or anxiety and that have examined mediators of psychological treatments. A group of 20 reviewers from the COST-Action TREATme (CA16102) divided into ten pairs independently screen studies for inclusion, extract information from the included studies, and assess the methodological quality of the included studies and the requirements for mediators. The methodological quality will be assessed by The Mixed Methods Appraisal Tool. Extracted data from the included studies will be collected and presented using a narrative approach. Discussion: This systematic review will summarize and provide a comprehensive overview of the current evidence on mediators of psychological treatments for anxiety and depression for adolescents and young adults. Results will allow the identification of strategies to optimize intervention to enhance clinical outcomes. Ethics and dissemination: Ethics approval is not required. Findings from this systematic review will be published in a peer-reviewed journal and disseminated at conferences and meetings. PROSPERO registration number: CRD42021234641.